Pelton Turbines - Zhang, Zhengji; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book concerns the theoretical foundations of hydromechanics of Pelton turbines from the engineering viewpoint. For reference purposes, all relevant flow processes and hydraulic aspects in a Pelton turbine have been analyzed completely and systematically. The analyses especially include the quantification of all possible losses existing in the Pelton turbine and the indication of most available potential for further enhancing the system efficiency. As a guideline the book therefore supports further developments of Pelton turbines with regard to their hydraulic designs and optimizations. It is thus suitable for the development and design engineers as well as those working in the field of turbo machinery. Many laws described in the book can also be directly used to simplify aspects of computational fluid dynamics (CFD) or to develop new computational methods. The well-executed examples help better understand the related flow mechanics.
Introduction -- Working principle of Pelton turbines -- Injector characteristics -- Jet characteristics and measurements -- Interaction between the jet and Pelton wheel -- Fluid mechanics in the rotating bucket -- Water spreading in the rotating bucket -- Exit flow conditions -- Exit flows and hydraulic losses -- Fricton effects and flow friction theorem -- Viscous cross-flow through the bucket -- Viscous longitudinal flow through the bucket -- Friction and windage losses in Pelton wheels -- Power loss due to bearing frictions -- Hydraulic and mechanical efficiency -- Real hydraulic efficiency characteristics -- Runaway speed and acceleration profile -- Hydraulic design of Pelton turbines -- Multi-jet Pelton turbines -- Geometric and hydraulic similarities -- Model turbine tests and efficiency scale-up -- Sand abrasion and particle motion in the bucket flow -- Bucket mechanical strength and similarity laws -- Appendices: Nomenclature -- Definition of derived parameters -- Specific speed and application in Pelton turbines -- Specification of the jet piece for a bucket -- Specification of the bucket positions -- Particle motion along the streamlines in the Pelton Bucket.
Keywords: Fluid mechanics; Machinery; Electric power production; Water; Hydrology; Engineering geology; Engineering Fluid Dynamics; Machinery and Machine Elements; Electrical Power Engineering; Mechanical Power Engineering; Water; Geoengineering